Islamic Movement in Sudan: its’ Development and Influence on the Dynamics of Sudan Education - Ribut Nur Huda (Islamic University of Indonesia, 2022)
The Islamic movement has occupied an important place in Sudan's educational world from its leadership in 1989 till the present. The role of the Islamic Movement seems imbalanced and causes influential people